Sediment, Nutrient, and Bacterial Runoff from Biosolids and Mineral Fertilizer Applied to a Mixed Cool- and Native Warm-Season Grassland in the Ozark Mountains - Cody B. Wallace; Michael G. Burton; Steven G. Hefner; Thomas A. DeWitt (Applied and Environmental Soil Science)
Rainfall simulations were conducted within mixed (cool- and native warm-season) grasslands in the sloping, rocky soils typical of the Ozark Mountains region to estimate nutrient and bacteria levels in runoff from biosolids and mineral fertilizer (MF). The ability of narrow (1 m) vegetated filter strips (VFS) to reduce losses was evaluated. Experiment 1 included an untreated control (C); 37 kg plant available nitrogen (PAN) ha−1 from biosolids applied to the upslope half of the plot with the downslope half serving as a VFS (LBF); 74 kg PAN ha−1 from biosolids, with VFS (HBF); and a uniform biosolids application at the lower rate and no VFS (LBU). Experiment 2 examined runoff from MF applied at 89 kg ammoniacal nitrogen (NH4-N) ha−1 and 147 kg phosphorous (P) ha−1 over the whole plot (MFW) or only on the upslope half (with VFS) (MFF). No significant differences were detected among mean fecal coliform levels despite large differences in magnitude. Losses of NH4-N and P were greater for LBU than for LBF. Although only marginally significant (P=0.058), total phosphorous contained in runoff was nearly three times higher in MFW than in MFF. Results of this study suggest that even a small VFS can potentially reduce nutrient levels in runoff.